Outsourcing: una metodología de negocios para la rentabilidad y competitividad en el sector textil peruano - Pasquel Velásquez, José Arnaldo (2007)
-- This work intends to illustrate how the application of the Outsourcing model (according to the Strategic Plan) can increase the competitiveness of a company. The case of the application of Outsourcing in Devanlay Peru, one of the main Peruvian textile export companies, will be developed step by step showing the fast growing of its business. There are important concepts which will be reviewed for a better understanding such as the Strategic Plan, Supply Chain, Value Chain, Competitiveness, Small Company, Basic and Fashion Garments, Cluster and Project Management. The Strategic Plan helps us define the objectives of the business. If the Outsourcing model needs to be applied, the Project Management (PMI or other) will lead us to a right planning, The knowledge of the global textile sector is essential to have a good analysis, this knowledge involves brand tendencies, workforce’s global context, the country’s competitiveness, new materials, the cluster, and the knowledge of the customer, factors that will help us make an appropriate decision.